Metformin inhibits 2D and 3D motility in astrocytoma cancer cells. (c2014) - Hassan, Marwa Fouad Al (2016)
Metformin is an oral anti-hyperglycemic agent in the biguanide class which lowers blood glucose concentrations and has been used to treat type 2 diabetes mellitus. Metformin is highly used in polycystic ovary syndrome (PCOS), premature puberty, and non-alcoholic fatty liver disease (NAFLD). A brain tumor is an intracranial solid neoplasm which is a tumor within the brain or the central spinal canal. According to the World Health Organization (WHO), primary brain tumors are classified according to their histological characteristics and cellular origin. In addition, gliomas, which belong to the neuroepithelial brain tumors, include oligodendroglioma, astrocytoma, ependymoma, mixed glioma, and glioblastoma. Previous studies showed a cytotoxic effect of metformin on ovarian cells. This prompted us, in our current study, to investigate the effect of metformin on the proliferation and metastasis astrocytoma. When this drug is applied, it led to a relative decrease in the proliferation of astrocytoma cancer cells. Metformin treatment also resulted in a drastic inhibition of 2D cell motility and an increase in cellular adhesion. Hence, our study shows that Metformin could be used as an anti-metastatic drug in brain tumor.